2016
DOI: 10.1038/srep26839
|View full text |Cite
|
Sign up to set email alerts
|

Donor CD47 controls T cell alloresponses and is required for tolerance induction following hepatocyte allotransplantation

Abstract: CD47-deficient hepatocyte transplantation induces rapid innate immune cell activation and subsequent associated graft loss in syngeneic recipients. However, the role of donor CD47 in regulation of T-cell alloresponses is poorly understood. We addressed this question by assessing OVA-specific immune responses in mice following hepatocyte transplantation from CD47-competent or -deficient OVA-transgenic donors. Compared to sham-operated controls, intrasplenic transplantation of CD47-deficient OVA+ hepatocytes sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Previously, we have demonstrated that HLA class I‐silenced cells have a superior capacity to escape antibody‐mediated, complement‐dependent and cellular‐dependent cytotoxicity in vitro and in vivo . Moreover, recent studies have shown that CD8 + T cells play an important role in cellular alloimmune responses against the transplanted hepatocytes . The decrease in proliferation observed in our MHLC, when HLA class I expression was down‐regulated, may indicate a lower activation of both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previously, we have demonstrated that HLA class I‐silenced cells have a superior capacity to escape antibody‐mediated, complement‐dependent and cellular‐dependent cytotoxicity in vitro and in vivo . Moreover, recent studies have shown that CD8 + T cells play an important role in cellular alloimmune responses against the transplanted hepatocytes . The decrease in proliferation observed in our MHLC, when HLA class I expression was down‐regulated, may indicate a lower activation of both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 87%
“…9,10,19 Moreover, recent studies have shown that CD8 + T cells play an important role in cellular alloimmune responses against the transplanted hepatocytes. 20,21 The decrease in proliferation observed in our MHLC, when HLA class I expression was down-regulated, may indicate a lower activation of both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies revealed that MDSC were required for the tolerance induction of hepatocyte transplantation and that CD47-deficient hepatocytes could not be tolerated and paradoxically stimulated antidonor T cell responses. 41 Here, we report that the SIRPα/CD47 pathway is crucial for the induction and the maintenance of established immune tolerance to kidney allograft and to prevent allograft rejection associated with increased macrophage infiltrates. We also describe that interrup- We also observed in vivo that administration of anti-SIRPα or anti-CD47 mAbs induced a decrease of MDSC in the blood of naïve or tolerant animals whereas total myeloid cells (expressing SIRPα as well) remained stable in leukocytes excluding any direct cytotoxicity of these mAbs.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers investigating the role of CD47, a member of the Ig superfamily which provides a protective signal against phagocytotic activity of macrophages, recently reported on the contribution of donor CD47 in the regulation of T-cell alloresponses in hepatocyte transplantation. Thru a collection of innovative experiments, they were able to show the important role that CD47 plays in the control of not only T-cell alloresponses but also tolerance induction following HT (97). This work, combined with other published works, adds to the building evidence that CD47 incompatibility may induce both innate and adaptive immune mediated rejection of transplanted hepatocytes (97101).…”
Section: Improving Transplanted Hepatocyte Survival and Monitoringmentioning
confidence: 99%
“…Thru a collection of innovative experiments, they were able to show the important role that CD47 plays in the control of not only T-cell alloresponses but also tolerance induction following HT (97). This work, combined with other published works, adds to the building evidence that CD47 incompatibility may induce both innate and adaptive immune mediated rejection of transplanted hepatocytes (97101). …”
Section: Improving Transplanted Hepatocyte Survival and Monitoringmentioning
confidence: 99%